Lack of TAFI increases brain damage and microparticle generation after thrombolytic therapy in ischemic stroke. Issue 2 (August 2015) - Orbe, J.; Alexandru, N.; Roncal, C.; Belzunce, M.; Bibiot, P.; Rodriguez, J.A.; Meijers, J.C.M.; Georgescu, A.; Paramo, J.A.
Abstract: Background: Thrombin-activatable fibrinolysis inhibitor (TAFI) plays an important role in coagulation and fibrinolysis. Whereas TAFI deficiency may lead to a haemorrhagic tendency, data from TAFI knockout mice (TAFI −/−) are controversial and no differences have been reported in these animals after ischemic stroke. There are also no data regarding the role of circulating microparticles (MPs) in TAFI −/−. Objectives: to examine the effect of tPA on the rate of intracranial haemorrhage (ICH) and on MPs generated in a model of ischemic stroke in TAFI −/− mice. Methods: Thrombin was injected into the middle cerebral artery (MCA) to analyse the effect of tPA (10 mg/Kg) on the infarct size and haemorrhage in the absence of TAFI. Immunofluorescence for Fluoro-Jade C was performed on frozen brain slides to analyse neuronal degeneration after ischemia. MPs were isolated from mouse blood and their concentrations calculated by flow cytometry. Results: Compared with saline, tPA significantly increased the infarct size in TAFI −/− mice (p < 0.05). Although plasma fibrinolytic activity (fibrin plate assay) was higher in these animals, no macroscopic or microscopic ICH was detected. A positive signal for apoptosis and degenerating neurons was observed in the infarct area, being significantly higher in tPA treated TAFI −/− mice (p < 0.05). Interestingly, higher numbers of MPs were found in TAFI −/− plasma as compared to wild type, after stroke (p < 0.05). Conclusions: TAFI deficiency results in increased brain damage in a model of thrombolysis after ischemic stroke, which was not associated with bleeding but with neuronal degeneration and MP production. Highlights: tPA treatment in TAFI deficient mice increases brain damage and neurodegeneration in a thromboembolic stroke model. No macroscopic or microscopic bleeding complications were detected after stroke in TAFI −/− mice. Higher numbers of MPs were found in TAFI −/− plasma as compared to wild type, after stroke.